Effect of Chemical Mutagen on Seed Germination, Morphological and Essential Oil Content in Ocimum basilicum L. - Kumari, Neha; Singh, Maneesha (Asian Journal of Biological and Life Sciences)
Sweet Basil (Ocimum basilicum L.) variability might be improved with hybrid combinations but combination breeding is a time-consuming process for genetic improvement of this useful plant due to smaller floral size and autogamy. Therefore, induced mutation is an important complementary breeding method for this plant to produce heritable changes both in the case of qualitative and quantitative traits. The present study has been carried out to induce variations in Ocimum basilicum L. using Ethyl Methane Sulphonate (EMS), a chemical mutagen with different doses to determine the rate of seed germination, survival rate, morphological characters, and essential oil content in expectation of finding desirable mutants. Results revealed that there were significant effects of EMS doses on seed germination, rate of plant survival at maturity, pollen viability, morphological characters and oil content. With the increase in EMS concentration, the rate of seed germination and pollen viability was significantly decreased. The present studies showed positive as well as negative effects of mutagenesis i.e. mutants with bushy appearance, increased height, number of primary branches and broad leaves, dwarf with small leaves, short internodes with few nodes, and reduction of seed size and ultimately low yield has been observed in O. basilicum L. Thus, these findings suggest that mutation breeding is an important method for improving crops and creating new genetic resources with desirable traits under diverse climatic conditions.
Keywords: Essential oil; Ethyl Methane Sulphonate (EMS); Ocimum basilicum L.; Pollen viability; Seed germination